Methodological Considerations for the Use of Longitudinal Interpretative Phenomenological Analysis in Healthcare Research - Marta Wanat; William Day; Michael Larkin (International Journal of Qualitative Methods)
Longitudinal Qualitative Research (LQR) aims to chronicle individuals’ lives in real-time, offering a “qualitative movie” of their unfolding experiences, focusing on the dynamic interplay of continuity and change. The rising interest in LQR has led to methodological advancements, with LQR being combined with established methodologies. Among these, Interpretative Phenomenological Analysis (IPA) has stated to engage with longitudinal design. IPA’s unique focus on idiography, phenomenology and hermeneutics can be particularly fruitful when engaging with temporal dimensions. Yet, applying longitudinal design to any qualitative study is complex; it requires thoughtful consideration of how we embed temporal lenses through the whole study cycle and goes beyond collecting data 'more than once’. The literature on the implications of embedding longitudinal design in IPA methodology is still developing. In particular, the considerations related to embedding temporality when approaching data collection have not yet been explored in detail. In this paper, we reflect on key considerations and strategies when conducting data collection as part of longitudinal IPA. We focus on the balance between flexibility and continuity when collecting data across sequential waves of data collection, and on the extent to which researchers explicitly engage with participants in uncovering continuity and change throughout their studies, which we discuss in turn. We do that by drawing on published papers, complemented by our own experience using IPA and LQR to illustrate the methodological dilemmas. By doing this, we hope to provide valuable insights for researchers considering the use of IPA and LQR and to facilitate an understanding of how these features can be integrated effectively throughout the research process.